Aerodynamics of symmetric permeable airfoils and wings: CFD simulation - Mohammed Aldheeb, Mohammed Abdulmalek; Asrar, Waqar; Omar, Ashraf Ali; Altaf, Afaq; Sulaeman, Erwin (Inderscience Enterprises Ltd., 2020)
Abstract: This paper presents a simple, and effective CFD modelling of a permeable thin symmetric, NACA 0008, 3D wing and airfoil at a Reynolds number of 3.45 × 105 using the StarCCM+ software. The results are validated against wind tunnel aerodynamic balance data. The aerodynamic performance of both permeable wing and airfoil is presented in terms of lift, drag, lift to drag ratio, and moment coefficients by varying permeability values and permeable sections. The lift slopes show good agreement with analytical and experimental data. The results show a decrease in drag at low values of permeability which results in an increase in the lift to drag ratio up to 72% for permeable airfoil and 65% for the permeable wing. A strong effect of permeability and its location on the pitching moment coefficient is observed, opening up avenues for the control of stability through permeability.